FAKTOR YANG MEMPENGARUHI AUDITOR SWITCHING TERHADAP PROPERTY DAN REAL ESTATE PERIODE 2017-2019 - Tengku Suripah Rani Mutiah; Riana Rachmawati Dewi; Rosa Nikmatul Fajri (Jurnal Proaksi, 2021)
Abstract This study aims to determine the effect of financial distress, KAP size, management turnover, audit opinion, and firm size on auditor switching. The population in this study is the Property and Real Estate companies on the Indonesia Stock Exchange (BEI) 2017-2019. The sample was selected by purposive sampling method and got 106 companies from several criteria. The data source is secondary data from the website (www.idx.co.id). This study uses logistic regression analysis with the help of SPSS version 21 program. The results show that firm size has an effect on auditor switching, while financial distress, KAP size, management turnover, and audit opinion have no effect on auditor switching. Keywords: auditor switching, financial distress, KAP size, management turnover, audit opinion